Discriminative stimulus properties of the 5-HT1A receptor biased agonists NLX-101 and F13714, in rats trained to discriminate 8-OH-DPAT from saline. Issue 8 (December 2021) - Broadbear, Jillian H.; Depoortere, Ronan Y.; Vacy, Kristina; Ralph, David; Tunstall, Brendan J.; Newman-Tancredi, Adrian
Abstract : NLX-101 and F13714 are selective, full efficacy, biased agonists of the serotonin (5-HT1A ) receptor. NLX-101 preferentially activates cortical postsynaptic 5-HT1A receptors, whereas F13714 preferentially activates raphe nuclei presynaptic 5-HT1A receptors. We compared NLX-101 and F13714 for their efficacy and potency to substitute for the discriminative cue produced by the prototypical, nonbiased 5-HT1A receptor agonist 8-OH-DPAT (racemate). Male and female Sprague–Dawley rats were trained to discriminate 8-OH-DPAT (0.1 mg/kg i.p., 20 min pretreatment) from saline using a classical two-lever drug-discrimination procedure. 8-OH-DPAT (0.01 and 0.05 mg/kg i.p.) dose-dependently substituted for the training dose, with about 50% responding on the 8-OH-DPAT-associated lever at 0.05 mg/kg. F13714 fully and very potently substituted for the training dose of 8-OH-DPAT from 0.018 mg/kg i.p., whereas NLX-101 only achieved full substitution at 0.5 mg/kg i.p., a dose which is known to also activate presynaptic 5-HT1A receptors. The 5-HT1A receptor partial agonist, buspirone, partially substituted (~80%) at 1 and 2 mg/kg i.p., doses which also decreased response rates. F13714 decreased response rates at 0.05 mg/kg. The selective 5-HT1A receptor antagonist WAY-100 635 (1 mg/kg s.c., 40 min pretreatment) elicited almost no responding on the 8-OH-DPAT-associated lever by itself, but blocked the discriminative stimulus effects produced by administration (20 min pretreatment) of 8-OH-DPAT (0.1 mg/kg), F13714 (0.025 mg/kg), NLX-101 (0.5 mg/kg) or buspirone (1 mg/kg). These data suggest that the discriminative cue produced by 0.1 mg/kg i.p. 8-OH-DPAT results from activation of presynaptic 5-HT1A receptors. They also further demonstrate the distinct profiles in behavioral models of 5-HT1A receptor-biased agonists.